1995
DOI: 10.1002/prep.19950200502
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Oscillations in Regenerative Liquid Propellant Guns

Abstract: The present paper deals with pressure oscillations in regenerative liquid propellant guns (RLPG) presenting the state‐of‐the‐art research into sources and control of these combustion instabilities. Pressure oscillations with amplitudes up to 50 % of mean pressure and frequencies up to 60 kHz or more are present in experimental data of RLPGs, especially at medium and large calibers. Amplitudes increase with the volumetric energy density of the liquid propellant and the mass flow rate during injection. Frequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…The initial variation in piston travel between 3 ms to 4.5 ms is attributed to a mass-spring reaction which can be eliminated by improving the initial ignitiona combustion reaction (6) . The potential of the lumped-parameter model is demonstrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The initial variation in piston travel between 3 ms to 4.5 ms is attributed to a mass-spring reaction which can be eliminated by improving the initial ignitiona combustion reaction (6) . The potential of the lumped-parameter model is demonstrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, reduction of pressure oscillations is possible by various ways. Approaches include (6) (a) mechanical devices to affect the break-up of the liquid jet, (b) chemical methods to increase the burning rate, and (c) dissipative mechanisms to absorb the pressure waves. For example, jet dispersers can dramatically lower the magnitude of the ®rst-radial mode, the dominant acoustic mode in RLPG pressure oscillations, and liners in the combustion chamber (see Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The burning of droplets is dominant in a RLPG [6] or liquid propellant rocket [7], and the liquid propellant needs to be atomized to droplets firstly. G. P. Wren [8] found that the pressure oscillation in a RLPG was related to acoustic modes and combustion noises, and that the oscillation can be mitigated by altering the combustion characteristics of liquid propellant or by decreasing the local accumulation of liquid propellant. T. P. Coffee [9] studied the effects of the breakup and combustion of propellant jet on the high-frequency pressure oscillations by the numerical simulation for the interior ballistic cycle of a RLPG.…”
Section: Introductionmentioning
confidence: 99%